2006
DOI: 10.1002/mc.20281
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of UVB‐induced and basal cyclooxygenase‐2 (COX‐2) expression by apigenin in mouse keratinocytes: Role of USF transcription factors

Abstract: Apigenin is a bioflavonoid with chemopreventive activity against UV- or chemically-induced mouse skin tumors. To further explore the mechanism of apigenin's chemopreventive activity, we determined whether apigenin inhibited UVB-mediated induction of cyclooxygenase-2 (COX-2) expression in mouse and human keratinocytes. Apigenin suppressed the UVB-induced increase in COX-2 protein and mRNA in mouse and human keratinocyte cell lines. UVB radiation of keratinocytes transfected with a mouse COX-2 promoter/luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 56 publications
(70 reference statements)
0
42
0
Order By: Relevance
“…More recently, our group has focused on the effects of apigenin treatment on keratinocytes exposed to UVB radiation (19,20). These reports have shown that apigenin treatment downmodulates both basal and UVB-induced cyclooxygenase (COX)-2 expression in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, our group has focused on the effects of apigenin treatment on keratinocytes exposed to UVB radiation (19,20). These reports have shown that apigenin treatment downmodulates both basal and UVB-induced cyclooxygenase (COX)-2 expression in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that apigenin treatment of cells results in a wide variety of antitumorigenic and chemopreventive actions (13)(14)(15)(16)(17)(18). More recently, we have focused our investigative efforts on determining the effects of apigenin treatment on keratinocytes exposed to UVB radiation (19,20), the primary causative agent of skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Some flavonoids can modulate these pathways, which in turn regulates gene expression and favors the inhibition of carcinogenesis [97]. Table 2 summarizes some studies demonstrating antiinflammatory mechanisms implicated in specific flavonoid chemoprevention [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157].…”
Section: Flavonoids Inflammation and Cancermentioning
confidence: 99%
“…One of the earliest events in the arterial wall in the initiation of atherosclerosis is the adherence of mononuclear cells to endothelium, which is triggered by a number of adhesion molecules such as P-selectin, E-selectin [161], vascular cell adhesion molecule-1 (VCAM-1) and Genistein Neutrophils [143] COX-2 inhibition Naringin Colon carcinogenesis [144] Tricin Adenoma in APC min mice [145] Genistein Human breast cancer cells [146] Apigenin UVB induced mouse skin tumors [147] Inhibition of PKC Apigenin Mouse skin tumors [148] Luteolin Skin tumor cell line [149] Quercetin Skin tumor cell line [149] Modulation of MAPK Genistein Prostate cancer [150] Apigenin Prostate cancer cells [151] Apigenin Breast carcinoma cells [152] Modulation of NF-jB Morin Different tumor cell lines [153] Genistein Prostate, breast and pancreatic Cancer cells [154][155][156] Apigenin Prostate cancer [157] intercellular adhesion molecule-1 (ICAM-1) [162]. These molecules are expressed by endothelial and/or vascular smooth muscle cells upon proatherogenic stimuli such as oxidized LDL or oxidative free radicals [163,164].…”
Section: Flavonoids Inflammation and Cancermentioning
confidence: 99%
“…Apigenin fed by gavage inhibits prostate tumor xenograft growth in mice through up-regulation of insulin-like growth factor-3 (12). Apigenin's chemopreventive activity in multiple organ sites is likely tied to its ability to modulate pathways involved in cell cycle control (12,19,20), apoptosis (12,16,21,22), and signal transduction (12,19,(23)(24)(25). Apigenin inhibits the activation of the phosphoinositide 3-kinase/Akt pathway in numerous cell types including prostate cancer cell lines (12,19), potentially by blocking the ATP binding site of phosphoinositide 3-kinase (26).…”
mentioning
confidence: 99%